Modulação neuro-hormonal - Silva-Cardoso, J. (2019)
The current paradigm of medical therapy for heart failure with reduced ejection fraction (HFrEF) is triple neurohormonal blockade with an angiotensin-converting enzyme inhibitor (ACEI), a beta-blocker (BB) and a mineralocorticoid receptor antagonist (MRA). However, three-year mortality remains over 30%. Stimulation of counter-regulatory systems in addition to neurohormonal blockade constitutes a new paradigm, termed neurohormonal modulation. Sacubitril/valsartan is the first element of this new strategy. PARADIGM-HF was the largest randomized clinical trial conducted in HFrEF. It included 8442 patients and compared the efficacy and safety of sacubitril/valsartan versus enalapril. The primary endpoint was the composite of cardiovascular mortality and hospitalization due to HF, which occurred in 914 (21.8%) patients receiving sacubitril/valsartan and in 1117 (26.5%) patients receiving enalapril (HR 0.8, 95% CI 0.73-0.87, p=0.0000002; NNT 21). Sacubitril/valsartan reduced both primary endpoint components, as well as sudden cardiac death, death due to worsening HF, and death from all causes. Patients on sacubitril/valsartan reported less frequent deterioration of HF and of quality of life, and discontinued study medication less frequently because of an adverse event. PARADIGM-HF demonstrated the superiority of sacubitril/valsartan over enalapril, with a 20% greater impact on cardiovascular mortality compared to ACEIs. Accordingly, in 2016, the European (ESC) and American (ACC/AHA/HFSA) cardiology societies simultaneously issued a class I recommendation for the replacement of ACEIs by sacubitril/valsartan in patients resembling PARADIGM-HF trial participants.